Lumen-apposing metal stents in interventional endoscopy: a state-of-the-art review with focus on technical and clinical successes and complications. Issue 1 (January 2020) - Kadah, Anas; Khoury, Tawfik; Mari, Amir; Mahamid, Mahmud; Sbeit, Wisam
Abstract : Endoscopic transmural drainage is considered the initial treatment option for pancreatic fluid collections. Recently, lumen-apposing metal stents have been introduced for pancreatic fluid collections drainage under endoscopic ultrasound guidance, in addition to evolving data in bile duct and gallbladder drainage. We aimed to perform systematic review with reporting pooled data analysis on technical success, clinical success and complications rate of endoscopic ultrasound-guided lumen-apposing metal stents uses. A MEDLINE/PubMed and EMBASE search for all studies on lumen-apposing metal stents uses in pancreatic, biliary and other indications was conducted. Data regarding safety, complications and yield were extracted and included in the final pooled analysis. Overall, 19 articles dealing with pancreatic fluid collections drainage, 18 articles reporting on bile duct drainage and 19 articles relevant to gallbladder drainage were identified. Technical and clinical successes in all disease conditions were high and reached more than 95%. Complications rate in pancreatic fluid collections, bile duct and gallbladder drainages were 12%, 11.2% and 9.8%, respectively. Endoscopic ultrasound-guided lumen-apposing metal stents is technically feasible with very high success rate and acceptable complications rate.